Double Stage Cumulative Shrunken Bayes Estimator for the variance of Normal distribution for equal volume of two sample (Baghdad Science Journal, 2012)
In this article we study the variance estimator for the normal distribution when the mean is un known depend of the cumulative function between unbiased estimator and Bays estimator for the variance of normal distribution which is used include Double Stage Shrunken estimator to obtain higher efficiency for the variance estimator of normal distribution when the mean is unknown by using small volume equal volume of two sample .